“Grupo Cultural Encanto do Quilombo”: uma etnografia da prática musical. - Farias, Marcos Alan Costa (2018)
This dissertation focuses on reflections on the musical practice of the “Encanto do Quilombo Cultural Group.” The group is composed of musicians who define themselves as quilombolas of Jauari, which is located along the Erepecuru River in the municipality of Oriximiná, Pará. This work results from fieldwork conducted at intervals between 2016 and 2018 that sought, by means of orality, to discuss elements relating to current musical practices. These elements include narratives of escape and the group’s organizational form, as well as knowledge and actions that consolidate and reaffirm ethnic identity. Thus, I researched the group's musical practice from an ethnomusicological perspective. In this way, it was possible to describe and analyze these quilombolas’ relationship with aspects surrounding the practice. In general, this work sought to reflect on music as a product of social relations among the quilombolas of Jauari. Ethnographically, it was possible to understand how music is re-signified. According to social agents, one of the main reasons for which the music is as it is today is based on the continuity of past musical practices; however, this does not mean that their music is a residue of the past. Music, as well as other practices, are present in their social memory and undergo a process of re-signification when new elements are inserted into the context. Therefore, this is a study of how music is contemplated, produced and practiced in Jauari and other places in which the group establishes relations.